Noget om Danmarks Handels-Omsætning, samt Told- og Consumtions-Indtægter i 1848. - Hald, J. C. (Tidsskrift for Landøkonomi, 2018)
Noget om Danmarks Handels-Omsætning, samt Told- og Consumtions-Indtægter i 1848.